Prolonged Neuromuscular Block Due to DrugDrug Interaction in a Post-Chemotherapy Patient Posted for Septoplasty: A Case Report - Chashamjotbawa,; Amandeepsingh,; Laveenadabla, (International Journal of Psychosocial Rehabilitation, 2020)
Introduction- It is not uncommon to encounter cancer patients who have been subjected to chemotherapy being planned for non-oncological surgery. Chemotherapeutic drugs stimulate a cascade of catastrophic events leading to apoptosis via drug-receptor interaction. We are presenting a case report on one such side-effect missed on the pre-operative assessment that led to prolonged recovery phase in a patient posted for septoplasty under general anesthesia.Case Report: A 62-year-old female planned for septoplasty had been on chemotherapeutic treatment for unilateral breast cancer stage 2. Drug-related toxicities were ruled out, and general anesthesia was planned. Premedication in the form of injection glycopyrrolate 0.005 mg/kg and fentanyl 1 microgram/kg; induction by injection propofol (total 90 mg); and succinylcholine 1.5 mg/kg. After securing ETT, maintenance was achieved with isoflurane and N20:O2 (50:50) with vecuronium used as NDMR. Post-cessation of surgery, which lasted for 1 hour 40 minutes, inhalational gases were stopped, but the patient remained deeply sedated and hypotonic despite reversal with neostigmine for 45 minutes. Thereafter, her eye opening returned, but her tachypnoea persisted, so she was bridged to BiPAP mode in the ICU till she regained muscle tone and distress subsided, which took around 2 hours. This delayed muscular recovery was thought to be due to cyclophosphamide-induced pseudocholinesterase inhibition, which caused the action of succinylcholine to be prolonged.Conclusion: Chemotherapeutic agents and their drug-drug interactions must be kept in mind while formulating plans of anesthesia for cancer patients undergoing surgery for general indications.